Nanostructured lipid carriers (NLC) for the delivery of natural molecules with antimicrobial activity: production, characterisation and in vitro studies. (2nd January 2017) - Cortesi, Rita; Valacchi, Giuseppe; Muresan, Ximena Maria; Drechsler, Markus; Contado, Catia; Esposito, Elisabetta; Grandini, Alessandro; Guerrini, Alessandra; Forlani, Giuseppe; Sacchetti, Gianni
Abstract: This study describes the preparation, characterisation and in vitro activity of nanostructured lipid carriers (NLCs) encapsulating natural molecules with antimicrobial activity, such as plumbagin, hydroquinon, eugenol, alpha-asarone and alpha-tocopherol. NLCs were prepared by melt and ultrasonication method, characterised by Cryo-TEM for morphology and SdFFF for dimensional distribution and active encapsulation yields. In vitro tests were conducted on bacteria, fungi and human cell cultures. In vitro tests demonstrated that plumbagin is strongly toxic towards F. oxysporum especially when active molecules are loaded on NLC. Plumbagin was completely non toxic on cyanobacterial model strain up to a threshold over which cell viability was completely lost. NLC loaded with active molecules showed a lower toxicity as compared to their free form on human cultured cells. Although further studies need to be performed, these systems can be potentially proposed to control phytopathogenic organisms.